2013
DOI: 10.1088/0953-2048/26/9/095011
|View full text |Cite
|
Sign up to set email alerts
|

Edge superconductivity in Nb thin film microbridges revealed by electric transport measurements and visualized by scanning laser microscopy

Abstract: The resistance R versus perpendicular external magnetic field H was measured for superconducting Nb thin film microbridges with and without microholes (antidots, ADs). Well below the transition temperature, integral R(H) measurements of the resistive transition to the normal state on the plain bridge show two distinct regions, which can be identified as bulk and edge superconductivity, respectively. The latter case appears when bulk superconductivity becomes suppressed at the upper critical field H c2 and belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
(81 reference statements)
2
9
0
Order By: Relevance
“…In perfectly uniform films SSC should not occur at perpendicular field orientation [1,16]. Yet, SSC in perpendicular fields has been directly visualized by scanning laser microscopy for similar films [21] and also reported for some layered supercondcutors [22] and sintered polycrystalline MgB 2 samples [23]. Presumably it is the polycrystallinity of our films that allows SSC at grain boundaries even in perpendicular fields.…”
Section: Discussionsupporting
confidence: 54%
“…In perfectly uniform films SSC should not occur at perpendicular field orientation [1,16]. Yet, SSC in perpendicular fields has been directly visualized by scanning laser microscopy for similar films [21] and also reported for some layered supercondcutors [22] and sintered polycrystalline MgB 2 samples [23]. Presumably it is the polycrystallinity of our films that allows SSC at grain boundaries even in perpendicular fields.…”
Section: Discussionsupporting
confidence: 54%
“…It was revealed that the H c3 /H c2 ratio is not a universal number but rather a complicated function that exhibits pronounced dependence on both T and the mean-free time τ mediated by disorder scattering. Niobium became essentially a paradigmatic material to study various phenomena associated with surface superconductivity and multiple experiments continue to follow [14][15][16][17][18][19][20]. Naturally over time experimental efforts on surface superconductivity branched into different directions.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown by Dieckmann et al 69 that this technique, lowtemperature scanning laser microscopy (LTSLM), delivers results that are equivalent to LTSEM. LTSLM has, among others, been applied to research on superconductors 32,34,70,71 , the quantum Hall effect 72 , spintronics 73,74 and spin-caloritronics 75 . The LTSPM can be operated in LTSLM mode to gain information on the electric trans- port properties of a sample.…”
Section: Imaging Of Electric Transport Propertiesmentioning
confidence: 99%